Efeitos da terapia fotodinâmica coadjuvante ao tratamento periodontal básico - estudos clínicos: revisão da literatura - Costa, Rafaela Mortari [UNESP] (2010)
The periodontal disease is a multifactorial inflammatory disease that affects the supporting tissues (periodontal ligament, cementum and alveolar bone), its main causative agent is the accumulation of plaque and can cause pocket formation in the gingival tissue, attachment loss, bone destruction and possible loss of the dental element. The main goal of periodontal treatment is to restore periodontal health by the removal of supra and subgingival bacterial deposits present on the root surface by scaling and root planing. However, the mechanical therapy of plaque removal may be impaired due to capacity, some microorganisms present, settling in areas inaccessible to periodontal instruments (eg, furcations, deep invaginations, and concavities) and invasion of pathogens into tissues surrounding soft. As adjunctive therapy to mechanical therapy, antimicrobials are used in the reduction of periodontal pathogens, but the indiscriminate use of antibiotics has led to the selection and bacterial resistance. Thus, the search for methods supporting periodontal treatment has increased in recent times. With the advent of low intensity laser (LLLT) and association with photosensitizing drugs (chromophores) was a new treatment option called Photodynamic Therapy (PDT). PDT is effective and biostimulator lethal action against microorganisms and cells that could be an alternative to the traditional use of antimicrobial agents in periodontal therapy. Faced with these facts constituted purpose of this study show a literature review on the effects of PDT adjunct to periodontal treatment in basic clinical studies. The literature review showed that photodynamic therapy has produced conflicting results regarding the improvement in clinical periodontal parameters (probing depth, clinical attachment level and bleeding), but it is clear its effect...